Pengaruh Metode Pembelajaran dan Kemampuan Berpikir Kritis Terhadap Kesadaran Sejarah Siswa SMA Islam Al Azhar Kelapa Gading Jakarta - Wage Wardana (Jurnal Pendidikan Sejarah, 2017)
The aim of study is to reveal the effect of learning methods and critical thinking style tostudent historical consciousness in Al Azhar Kelapa Gading Senior High School Jakarta. Thisresearch used is the experimental method. Research instrumentation will include a test that will beused to measure students history awareness from instructional methods and critical thinking style ofstudents. As for out come of this research are : (1) Student’s historical consciousness who are usingthe problem solving method will higher than students who used conventional method, (2)There is aninteraction between learning method and critical thinking style toward historical consciousness, (3)Student’s historical consciousness who have a high critical thinking and use a problem solvingmethod are higher than students who have a high critical thinking style using a conventional method,(4) Student’s historical consciousness who have a low critical thinking style and using a problemsolving methods are lower than students who have a high critical thinking style using a conventionalmethods.